Histone acetyltransferase TaHAG1 acts as a crucial regulator to strengthen salt tolerance of hexaploid wheat. Issue 4 (23rd April 2021) - Zheng, Mei; Lin, Jingchen; Liu, Xingbei; Chu, Wei; Li, Jinpeng; Gao, Yujiao; An, Kexin; Song, Wanjun; Xin, Mingming; Yao, Yingyin; Peng, Huiru; Ni, Zhongfu; et al.
Abstract : A histone acetyltransferase contributes to salt tolerance by mediating reactive oxygen species production in hexaploid wheat, which is involved in salt stress adaptability of polyploidy wheat. Abstract: Polyploidy occurs prevalently and plays an important role during plant speciation and evolution. This phenomenon suggests polyploidy could develop novel features that enable them to adapt wider range of environmental conditions compared with diploid progenitors. Bread wheat ( Triticum aestivum L., BBAADD) is a typical allohexaploid species and generally exhibits greater salt tolerance than its tetraploid wheat progenitor (BBAA). However, little is known about the underlying molecular basis and the regulatory pathway of this trait. Here, we show that the histone acetyltransferase TaHAG1 acts as a crucial regulator to strengthen salt tolerance of hexaploid wheat. Salinity-induced TaHAG1 expression was associated with tolerance variation in polyploidy wheat. Overexpression, silencing, and CRISPR-mediated knockout of TaHAG1 validated the role of TaHAG1 in salinity tolerance of wheat. TaHAG1 contributed to salt tolerance by modulating reactive oxygen species (ROS) production and signal specificity. Moreover, TaHAG1 directly targeted a subset of genes that are responsible for hydrogen peroxide production, and enrichment of TaHAG1 triggered increased H3 acetylation and transcriptional upregulation of these loci under salt stress. In addition, we found the salinity-induced TaHAG1-mediated ROS production pathway is involved in salt tolerance difference of wheat accessions with varying ploidy. Our findings provide insight into the molecular mechanism of how an epigenetic regulatory factor facilitates adaptability of polyploidy wheat and highlights this epigenetic modulator as a strategy for salt tolerance breeding in bread wheat.